Evaluasi Implementasi Kurikulum Merdeka dalam Pembelajaran Sosiologi di SMA Negeri Kota Karanganyar - Indy Septyani, Fatikha; Asyalia Rachma, Dhela; Wahyuningrum, Rahma; Sinta Dewi, Olivia (Universitas Muhammadiyah Sorong, 2024)
This research aims to evaluate the implementation of the Merdeka Curriculum implemented in sociology learning in public high schools in Karanganyar City. Research data were obtained from two public high schools in Karanganyar City, Karanganyar Regency, which were the research subjects. This research uses a qualitative approach with a method in the form of a case study. This study uses Talcott Parsons' functional structural theory and the AGIL framework to evaluate the implementation of the Merdeka Curriculum. The data sources used, namely primary obtained through observation, interviews, and questionnaires and secondary obtained through literature studies related to the implementation of the Merdeka Curriculum. The results showed that the implementation of the Merdeka Curriculum in sociology learning in two public high schools in Karanganyar City was not considered optimal because the majority of sociology teachers felt that they still had difficulties in understanding and implementing the Merdeka Curriculum, so that in the implementation of learning, several obstacles were still found, including teachers not optimally utilizing innovative learning media, not implementing differentiated learning because it was considered difficult, and rarely using project-based learning because it was considered to hinder the next material. Therefore, it is necessary to increase understanding and training for teachers to support a more effective implementation of the Merdeka Curriculum, as well as the development of learning resources that support the implementation of the Merdeka Curriculum.